School-age children's perception of the hospital experience. (June 2017) - Boztepe, Handan; Çınar, Sevil; Ay, Ayşe
In order to determine the perception of hospital experiences among school-age children's (6–12 years), a descriptive and cross-sectional study was performed in 130 children hospitalized in a pediatric hospital with different diagnoses. Data were collected using a pediatric information form, questionnaire form, scale for attitudes towards hospital and healthcare personnel, and sources of anxiety generating thoughts scale (SAGTS). Children's expectations of the nurses were to be well treated (62%), to perform painless procedures (20%), to play games together (12%), to be capable of their job (10%), and to be cheerful (10%). Children's expectation of the hospital facilities was the availability of playgrounds and toys (19.2%), large and single rooms (15.4%), rooms with private bathroom (9.2%), and rooms with a television and Internet access (7.7%). A statistically significant, negative, and moderate linear relationship was found between the scale for attitudes towards hospital and healthcare personnel and SAGTS ( p < 0.05, r : −0.296). The present study was performed to define the children's hospital experiences, keeping in mind that the best opinion on this matter is the child's own opinion. The foundation of this understanding depends on admitting that the children can express their own opinions about the care they receive.